A novel nonsense mutation in the fumarate hydratase gene in a Chinese patient with recurrent leiomyomas - Yiyin Ruan, B.Sc.; Weiwei Feng, M.D., Ph.D.; Chenmin Yang, M.D., Ph.D. (F&S Reports, 2023)
Objective: To describe a novel nonsense mutation in the fumarate hydratase (FH) gene in a Chinese patient with recurrent multiple leiomyomas. Design: Case report. Setting: Medical school-affiliated tertiary hospital. Patient(s): A nulligravida patient aged 30 years with large uterine leiomyomas (ULMs) and severe anemia. Intervention(s): Clinical evaluation, abdominal myomectomy, targeted next-generation sequencing. Main outcome measure(s): Fumarate hydratase gene mutation in ULMs. Result(s): A novel nonsense mutation (c.771T>G) in the FH gene was identified in this patient. This mutation is located in exon 6, which encodes the N-terminal fumarate lyase domain. It leads to a predicted truncated protein with loss of the majority of the lyase domain, resulting in FH deficiency. Conclusion(s): Because of the recurrent multiple leiomyomas, this patient received 2 myomectomies within 5 years. On immunostaining the leiomyoma, FH deficiency was detected, and targeted next-generation sequencing revealed a novel mutation of the FH gene. This patient was at risk for early disease relapse and developing renal cancer, and close disease monitoring is recommended. Meanwhile, the expanded mutation database should benefit patients in diagnosing FH gene-associated ULMs.